Dairy cattle systems in Morocco as affected by structural adjustment policies - Sraïri M.T. (Mediterranean livestock production: uncertainties and opportunities, 2008)
Since the early eighties, structural adjustment policies have been applied to the agricultural sector in Morocco. This has progressively led to the suppression of all kinds of incentives at farm level. As a consequence, cattle systems have been forced to adapt themselves to survive. This paper discusses the diversity of dairy cattle production systems in Morocco. It analyses their functioning parameters (feeding, reproduction, rearing practices) and the productive performances (milk yield per cow, meat production) they achieve. It also evaluates their gross profitability. Then, the perspectives of the economic sustainability of each system are analysed in the frame of the on-going changes affecting the local milk market (free trade agreements). Finally, recommendations are made to assist the prevailing cattle systems in coping with these structural changes. Depuis le début des années '80', des politiques d'ajustement structurel ont été appliquées au secteur agricole au Maroc. Cela a induit un gel progressif de toute subvention à l'échelle des exploitations agricoles. Les systèmes d'élevage bovin laitier ont ainsi été contraints de s'adapter pour survivre. Cet article présente la diversité des systèmes bovins au Maroc. Il décrit leurs performances techniques (rendement laitier et production de viande) et leur rentabilité, à la lueur de l'analyse de leurs paramètres de fonctionnement (alimentation et reproduction). Les perspectives de durabilité économique de chacun de ces systèmes sont ensuite discutées, eu égard aux changements actuels affectant le marché local des produits laitiers (ouverture des frontières). Finalement, des recommandations sont présentées pour assister les systèmes d'élevage bovin laitier à composer avec la nouvelle conjoncture.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)